Treatment for Relapsed/Refractory Acute Myeloid Leukemia. Issue 6 (1st June 2021) - Thol, Felicitas; Heuser, Michael
Abstract : Patients with relapsed or refractory (r/r) acute myeloid leukemia (AML) have a poor prognosis and treatment remains challenging. For the majority of r/r patients, allogeneic hematopoietic stem cell transplantation (HSCT) is the only curative treatment approach. Salvage therapy is given in order to reduce the leukemia load prior to transplantation. Patients achieving complete remission prior to allogeneic HSCT have a more favorable outcome. Intensive salvage regimens commonly consist of an anthracycline and high-dose cytarabine backbone. Donor lymphocyte infusions have shown efficacy in patients relapsing after allogeneic HSCT. For patients who cannot be intensively treated (eg, elderly AML patients), outcome is generally very poor and combinations with novel agents are currently under investigation. Mutational analysis should be repeated at the time of relapse to identify aberrations that can be targeted with new agents. For r/r AML patients with mutated fms-related tyrosine kinase 3 ( FLT3 ), gilteritinib has shown superior results to intensive salvage regimens. The US Food and Drug Administration (FDA) and European Medicines Agency (EMA) approved gilteritinib for FLT3 mutated r/r AML patients. Ivosidenib and enasidenib, inhibitors for mutated isocitrate dehydrogenase ( IDH ) 1 and 2, respectively, have received approval for IDH1 / IDH2 mutated r/r AML by the FDA (not EMA). APR-246 restores the function of mutated TP53 and early study results are promising. Other agents targeting CD47, menin, neural-precursor-cell-expressed developmentally down-regulated 8, as well as bispecific antibodies or chimeric antigen receptor T cells are under investigation. Further trials are needed to understand how to best combine novel agents with each other or with chemotherapy.